The research of antennas on the cold plasma - Ovsyanikov, V. V.; Jakimenko, S. V.; Moroz, S. M. (Видавництво Національного університету "Львівська політехніка", 2009)
The results of researches internal and external characteristics of loop and rod antennas on the basis of cold plasma gas discharge are presented. The rows of advantages of such antennas above the metallic ones have been pointed.
Keywords: сold plasma; loop plasma antenna; rod plasma antenna; radiation pattern; standing wave ratio on voltage; antenna gain; antenna efficiency